Aplikasi Game Tebak Gambar Menggunakan Bahasa Inggris Sebagai Media Belajar Siswa SD Bumi Ayu Berbasis Android - Puspitasari, Tuti; Tri Handayani, Lilis; Mahardika, Fajar Hari (YHMM PUBLISHING, 2025)
This study aims to develop an Android-based educational game application that uses an English picture guessing method as a learning medium for elementary school students at SD Bumi Ayu. The application is designed to enhance students’ interest and understanding of English vocabulary through an interactive and engaging approach. The development process follows the Waterfall model, consisting of requirement analysis, design, implementation, testing, and maintenance. The testing results show that the application performs well on various Android devices and receives positive feedback from both students and teachers. The use of attractive images and visual-based quiz challenges is considered effective in helping students learn and retain English vocabulary. Therefore, this application has the potential to serve as an alternative learning tool that supports teaching and learning processes at the elementary school level.